Absence of Neurobehavioral Disturbance in a Focal Lesion of the Left Paracentral Lobule - T. Imamura; K. Tsuburaya (Behavioural Neurology)
The case of a right-handed woman with an infarcation confined to the left paracentral lobule and sparing the supplementary motor area (SMA) is reported. She presented with a right leg monoplegia and displayed no mutism. The absence of any associated neurobehavioral disturbances (mutism, forced grasping, reduced spontaneous arm activity or aphasia raises the possibility that the left SMA has discrete neurobehavioral functions.